Two arrays of defense strategies of Brassicaceae plants that eavesdrop on mint volatiles - Satoru Sukegawa; Gen-ichiro Arimura (Journal of Plant Interactions, 2019)
Brassica rapa can eavesdrop on volatile compounds emitted from peppermint and consequently boost its defense responses against Plutella xylostella. In the current study, to assess how B. rapa receiver plants cultivated near peppermint plants resist P. xylostella, two biological assays were conducted. The data showed that the receiver plants cultivated with peppermint exhibited lower weight gain of P. xylostella larvae, compared to that exhibited by non-receiver plants. Moreover, a lower rate of oviposition of adult female P. xylostella was observed on B. rapa plants cultivated with peppermint plants compared to the rate on B. rapa plants cultivated with glass-enclosed peppermint plants, although receiver B. rapa plants that had been previously incubated with peppermint for 7 days and non-receiver B. rapa plants exhibited similar rates of oviposition. Taking all these findings together, we conclude that cultivation of B. rapa receiver plants with peppermint results in two arrays of defense strategies.